Listed Real Estate as an Inflation Hedge Across Regimes - Jan Muckenhaupt; Martin Hoesli; Bing Zhu (The Journal of Real Estate Finance and Economics, 2023)
This paper examines the inflation-hedging capability of listed real estate (LRE) companies in the US from 1975 to 2023, and in three other economies—the UK, Japan, and Australia—from 1990 to 2023. By using a Markov switching vector error correction model (MS-VECM), we identify that the short-term hedging ability moves towards being negative or zero during turbulent periods. In stable periods, LRE provides good protection against inflation. In the long term, LRE offers a good hedge against expected inflation and shows a superior inflation hedging ability than stocks. Additionally, we identify inflation-hedging portfolios by minimizing the expected shortfall. This inflation-hedging portfolio allocation methodology suggests that listed real estate stocks should play a significant role in investor portfolios.
Keywords: G11; G15; 330; Inflation Hedging; Listed Real Estate Companies; Markov-Switching; VECM; Inflation-Hedging Portfolio